Chinese Agricultural Engagement in Zambia: A Grassroots Analysis - Solange Guo Chatelard; Jessica M. Chu (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2015)
Recent focus on large-scale Chinese investments in African agriculture has fueled popular misperceptions of Chinese "land grabs" and has overshadowed another unexplored -and perhaps more significant-phenomenon: the rise of medium-scale private Chinese farmers and rural entrepreneurs. Despite growing research in the field, few reports thus far have examined what individual Chinese actors and investors are actually doing-or not doing-on the ground, or measured the implications of these activities for agricultural development. By examining the diverse scale and nature of Chinese agricultural investments in Zambia, and by situating these different forms of engagement within the broader context of the commercialization of agriculture, this brief reveals a complex picture of overlapping agricultural dynamics and interests.
Keywords: 330